Validation and adjustment of modified Erasmus GBS outcome score in Bangladesh. Issue 8 (30th July 2022) - Papri, Nowshin; Doets, Alex Y.; Mohammad, Quazi D.; Endtz, Hubert P.; Lingsma, Hester F.; Jacobs, Bart C.; Islam, Zhahirul
Abstract: Objective: We have assessed and improved the performance of the modified Erasmus GBS Outcome Score (mEGOS) among patients with Guillain‐Barré syndrome (GBS) from Bangladesh. Methods: Validation cohort consisted of patients with GBS from two prospective cohort studies in Bangladesh. Poor outcome was defined as being unable to walk independently at week 4 and week 26. We excluded patients able to walk independently, patients who died within the first week, or with missing GBS disability scores. Performance of mEGOS at entry and week 1 was determined based on the discriminative ability (ability to differentiate between patients able and unable to walk independently; measured using the area under the receiver operating characteristic curves [AUC]) and calibration (observed probability versus predicted probability of poor outcome). Results: A total of 506 patients aged ≥6‐year‐old were enrolled, with 471 and 366 patients included in mEGOS validation analysis at entry and week 1, respectively. The AUC values for predicting poor outcome (1) at week 4 were 0.69 (mEGOS entry) and 0.78 (mEGOS week 1) and (2) at week 26 were 0.67 (mEGOS entry) and 0.70 (mEGOS week 1). Mean predicted probabilities of poor outcome corresponded with observed outcomes except for the probability of poor outcome at week 4 which was overestimated by mEGOS week 1. This was resolved by updating the model intercept. Interpretation: The mEGOS shows valid outcome predictions among patients with GBS from Bangladesh. The model can aid the identification of patients at high risk of poor outcome and help to adequately allocate healthcare resources in low‐resource settings.